2015
DOI: 10.1002/cbic.201500245
|View full text |Cite
|
Sign up to set email alerts
|

Direct Chemical Activation of a Rationally Engineered Signaling Enzyme

Abstract: Few chemical strategies for activating enzymes have been developed. Here we show that a biarsenical compound (FlAsH) can directly activate a rationally engineered protein tyrosine phosphatase (Shp2 PTP) via disruption of autoinhibitory interactions between Shp2’s N-terminal SH2 domain and its PTP domain. We find that introduction of a tri-cysteine motif at a loop of Shp2’s N-SH2 domain confers affinity for FlAsH; binding of FlAsH to the cysteine-enriched loop relieves Shp2’s inhibitory inter-domain interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…applied the “bump-hole” approach of allele-specific kinase inhibition to PTPs. They sensitized PTPs to biarsenical compounds creating via mutagenesis strategies non-natural allosteric-inhibition sites or changing the active sites, thereby controlling the function of each cellular phosphatase by designing selective mutant/inhibitor pairs. , Interestingly, recently they were able to apply that approach to create a SHP2 mutant that is activatable through binding of biarsenical compounds, showing the versatility of this approach.…”
Section: A Brief Guide To the Classification And Resources Of Phospha...mentioning
confidence: 99%
“…applied the “bump-hole” approach of allele-specific kinase inhibition to PTPs. They sensitized PTPs to biarsenical compounds creating via mutagenesis strategies non-natural allosteric-inhibition sites or changing the active sites, thereby controlling the function of each cellular phosphatase by designing selective mutant/inhibitor pairs. , Interestingly, recently they were able to apply that approach to create a SHP2 mutant that is activatable through binding of biarsenical compounds, showing the versatility of this approach.…”
Section: A Brief Guide To the Classification And Resources Of Phospha...mentioning
confidence: 99%
“…Along these lines, we recently reported that a biarsenical compound (FlAsH-EDT 2 ) can directly activate a mutant of the PTP SHP2 through disruption of autoinhibitory interactions between SHP2’s N-terminal Src-homology 2 (SH2) domain and its PTP domain. [9] Unfortunately, the strategy developed for SHP2 activation is not broadly applicable across the PTP family, as only two of the 37 human classical PTPs utilize SH2-mediated autoinhibition. [4a] …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, we have attempted to develop methods for engineering activatable PTPs that retain wild-type-like enzymatic activities and regulatory-control mechanisms until a small-molecule activator is administered 30,31 . In this vein, we recently reported that the phosphatase PTP1B can be rendered activatable by targeting the enzyme’s WPD loop, a structural feature that is conserved among classical PTPs 31 .…”
Section: Introductionmentioning
confidence: 99%